(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Under nutrition during any period of childhood, even for relatively short term episodes, canhave negative effects on the cognitive development thus leads to poor school performance amongchildren. The research question is- does the mid-day meal scheme have an impact on the nutritionalstatus of school children (6-12 years) in Agra? This was a cross-sectional study conducted at threegovernment primary schools Mid Day Meal (MDM) in urban areas and three primary schools in ruralareas in Agra district. Simple random sampling was used for selection of children. Study variables takenwere height, weight and general physical examination. Results of the study indicated that the nutritionalstatus of MDM children. The reason for poor result for schools providing Mid Day Meals could beirregular attendance of children in school, less amount of Mid Day Meal, poor quality of food items in MidDay Meals, combined teaching of different standard, lack of class room etc. All these parameters need tobe further studied and evaluated for these impacts on academic achievement